Islamic Law Perspective on Civil Servant Divorce Process (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2021)
The aim of this study is to understand Islamic Law Perspectives on the divorce that is carried out by the government employees in Palu. This study used a qualitative field research. The research procedure that produces descriptive data in the form of writing and attitudes that can be observed from the subject itself. The data sources were obtained from primary and secondary data collected by observation, interviews and documentation. The data analysis techniques used were inductive and continuous using data reduction, data presentation and drawing conclusions or verification. The results show that the government employees who will conduct a divorce must obtain permission from the competent superior, which is then processed at the Regional Civil Service Agency, then the application process or divorce suit will be continued at the Palu Religious Court Class I A. As for legal review Islam regarding the divorce process of the State Civil Apparatus (ASN) is in accordance with Islamic law based on the word of Allah in QS An-Nisaa: (4): 59 and the complicating principle contained in the divorce process of the State Civil Apparatus (ASN) is in line with Islamic law as in the hadith of the prophet, namely From Ibn Umar. He said that Rasulullah Saw. has said, “that which is lawful which God hates most is divorce”. By understanding this hadith, Islam encourages the realization of a happy and eternal marriage, this is also contained in Law 1 of 1974 concerning the purpose of marriage, namely to form a happy and eternal family (household) based on one Godhead.